Development of School Exam Administration Based on LCDP with Scrum Method: An Innovation in Administrative Efficiency in Education - Anggraeni, Lia; Dliyaul Haq, Muh; Harliati Putri Pertiwi (Universitas Negeri Semarang, 2024)
Purpose: This study aims to explore the potential benefits of integrating innovative technology and agile methodologies, precisely the Scrum method and the AppSheet platform, to enhance the efficiency and effectiveness of school exam administration. The research seeks to address the constraints of manual exam administration and investigate the role of technology in providing practical and efficient solutions. Methods: The study was conducted at Sekolah Indonesia Kota Kinabalu, Sabah, Malaysia, utilizing the Scrum method with the AppSheet platform. The development of the school exam administration application with AppSheet, the low-code development platform (LCDP), using the Scrum method was carried out with a structured and adaptive approach. User stories and use case diagrams were employed to translate user insights into tangible visualizations, ensuring alignment with the intricate needs of the examination committee. Result: Implementing the Scrum methodology in the development process has proven effective in creating a tailored and efficient application for school exam administration. The application's design and functionality have been carefully crafted to meet the specific requirements of exam administration, including form-filling, data entry, PDF report generation, and user feedback collection. The user survey conducted as part of the development process has provided valuable insights into user experiences, guiding areas for improvement and ensuring a user-centric approach to application development. Novelty: This study contributes to the field by demonstrating the successful integration of agile methodologies and user-centric design principles in developing a comprehensive solution for school exam administration. The research highlights the potential of innovative technology to revolutionize exam administration for improved educational outcomes, emphasizing the significance of the Scrum methodology and the AppSheet platform in providing a structured yet adaptive approach to application development in the education sector.